Liar's Creek : a novel - Goldman, Matt, 1962- (Clay Hawkins, 2026)
"From New York Times bestselling author and Emmy Award-winner Matt Goldman comes Liar's Creek, which asks how far we'll go to protect the people we love. Riverwood, Minnesota is a scenic town threaded with trout streams carving their way through limestone bluffs. But beneath its picturesque facade, danger runs rampant. Clay Hawkins isn't a stranger to the secrets of his hometown. After twenty years away, Clay has recently returned home from abroad with his twelve-year-old son, and his relationship with his father, the recently replaced sheriff, is as strained as ever. But when Clay's beloved uncle disappears, the three generations of Hawkinses must overturn every stone in Riverwood and confront deep familial wounds to find the one person who brings them together. As danger looms, Clay worries that it might be too late to save his uncle--and that the rest of the family might be next"--